(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:N-RAS mutations are the most commonly detected molecular abnormalities in hematologic malignancies, especially in those of myeloid origin. Objective:Current study aimed to determine the frequency of N-RAS mutation and its correlation with P21N-RAS protein expression in patients with acute myelogenous leukemia (AML) in Iraq. Methods: Peripheral blood, bone marrow aspirate and biopsy samples were taken from 58 newly diagnosed AML patients (57 de novo and 1 therapy related AML) and 30 individuals with reactive bone marrow conditions were selected as a control group. Samples screened for N-RAS gene mutations using nested PCR followed by mutation sensitive digestion analysis (MSDA), and immunohistochemical analysis of P21N-RAS protein expression by using anti N-RAS monoclonal antibody. Results:N-RAS mutations at the time of diagnosis were found in 10/58 (17.24%) and P21N-RAS expression found in 5/58 (8.62%) patients with AML. There was a significant difference (P = 0.001) in P21N-RAS expression between mutant and wild type N-RAS patients with AML. No N-RAS mutations or P21N-RAS expression detected in the control group individuals. Conclusion:It can be suggested that there is activation of RAS-signaling cascade in AML patients, this is may support their role in molecular pathogenesis of acute leukemia. Also, there was a significant difference between N-RAS gene status and P21N-RAS protein expression in patients with AML. Keyword: AML, N-RAS Mutation, MSDA, P21N-RAS expression, Digital analysis.